mHealth education for patients with chronic kidney disease: protocol for a scoping review - Anders Nikolai Ørsted Schultz; Kristian Kidholm; Jan Dominik Kampmann; Caroline Moos; Eithne Hayes Bauer (BMJ Open)
Introduction More than 10% of the population worldwide is affected by chronic kidney disease (CKD). Despite many promising indications regarding the use of mHealth education for patients with CKD, there is still little evidence regarding the feasibility, effectiveness outcomes and outcome measures. Therefore, we will conduct a scoping review to examine the currently available evidence on mHealth education for patients with CKD and, thus, explore the existing evidence regarding feasibility, effectiveness outcomes and outcome measures, patient and/or provider perception and implementation challenges.Methods and analysis A scoping review will be conducted in accordance with Joanna Briggs Institute Manual for Evidence Synthesis chapter on scoping reviews.MEDLINE, Embase, CINAHL and PsycINFO will be searched. The search strategy will consist of blocks, which have been adopted and modified from former Cochrane reviews. Two independent reviewers will screen studies. Characteristics of the included studies, both quantitative and qualitative, will be reported using quantitative descriptive statistics. Quantitative results will be grouped by objectives (feasibility, effectiveness outcomes and outcome measures, patient perception and implementation challenges), types of intervention and characteristics of participants. Qualitative results will be organised into categories using an iterative process, as suggested by Pollock et al.Ethics and dissemination As this scoping review does not involve primary data collection, ethical permission is unnecessary. Results of the scoping review will be published in an international peer-reviewed scientific journal.Trial registration number Open Science Framework (https://osf.io/gxkeh/).